STRATEGIES OF ISLAMIC EDUCATION TEACHERS IN CHARACTER BUILDING OF STUDENTS - Agusyanto; Sinta Bela (Tsaqofah : Jurnal Pendidikan Islam, 2024)
Human beings, as educable and educating entities, are central to educational endeavors involving educators and learners. Education is a process of facilitating learners' maturation through guidance and direction. Islamic education teachers play a pivotal role in enhancing learners' knowledge and comprehension of Islamic teachings. The moral development of learners is significantly influenced by their environment, and the absence of Islamic education teachers and parents can hinder this development. This study investigates the strategies employed by Islamic education teachers in cultivating students' character at SMA Negeri Grujugan Bondowoso during the 2023/2024 academic year. Utilizing a qualitative-descriptive approach, this research collects and analyzes non-numerical data through observation, interviews, and document analysis. The researcher serves as the primary instrument, and data analysis involves reduction, presentation, and interpretation. The findings reveal that the Islamic education teachers at SMA Negeri Grujugan Bondowoso employ a 5S strategy (smile, greeting, greeting, polite, courteous) to foster students' character. These teachers play a crucial role in shaping students' moral compass, and their influence is highly valued by the students." Keywords: Strategies of Islamic Education Teachers, Character Development